Answer:
A
Explanation:
I just took the test on edgenuity.
Solve for the inverse:
(x-6)(x-6)=x squared -12x +36
36 + ? = 58
58-36= 22
That gives us (x-6) squared + an additional 22 so we have a total of 58.
Then (x-6) gives you the restriction since the vertex would be at (6,22).
X=6
X is greater than or equal to 6. This eliminates the bottom two options.
This leaves A and B. The only difference between them is adding or subtracting 6 from the square root. I put 6+ because we want an answer that is greater than 6 (which was the restriction).
So, the overall answer would be A:
x is greater than or equal to 6 and f(x)=6+ square root of x-22